POLA PEMBIASAAN IBADAH DI RUMAH PADA ANAK USIA DINI DI MASA PANDEMI COVID-19 - Safrizal Safrizal; Resti Yulia; Dadan Suryana (Tarbiyatuna Kajian Pendidikan Islam, 2021)
During a pandemic, the existence of a family is very important because it involves learning patterns that were initially carried out face-to-face, now they are carried out using the home learning method. So, it takes an active role of parents in the learning process carried out at home. The purpose of this study is to describe the optimization of the habit of worship at home in the framework of the concept of learning from home during the pandemic. The type of research used is qualitative with the type of case study. This research tries to describe in depth the optimization of the habituation of worship at home in AUD. The data was collected through three stages, namely in-depth interviews, observation, and documentation of habituation activities. The data that has been collected is analyzed using the method proposed by Miles and Huberman which consists of data reduction, data display and conclusion. In the process of ensuring data validity, researchers used triangulation techniques. The results showed that the optimization of the habituation of worship was carried out in three ways, namely controlling the congregational prayer time at home, accompanying the memorization process, and family gathering activities using the cooking method together. So it can be concluded that optimizing the habituation of worship at home essentially utilizes the amount of time spent with children in building closeness, so that the learning process at home in a pandemic period goes well.